DULCET: Valorization of Rambutan (Nephelium lappaceum) Seed Waste into Herbal Tea as an Environmental Education Project - Zahira Kanaya Prahita Awang; Zilda Syafira; Nasya Kinantri Basuki; Marliana Seny Aprilia Fadhilah; Aisya Afifah Fakhira; Nisrina Meta Gamanik (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
Organic waste generated by local sweet shops contributes to environmental pollution, particularly through the disposal of fruit seeds. Rambutan ( Nephelium lappaceum ) seeds are commonly discarded despite being reported in previous studies to contain bioactive compounds such as flavonoids, tannins, and polyphenols. This study aimed to explore the utilization of rambutan seed waste as an herbal tea product through a student-based environmental education project. The study employed a school-based observational approach combined with literature analysis. Rambutan seeds were collected from a local sweet shop, processed through drying and roasting, and brewed into tea infusions. Butterfly Pea Flower ( Clitoria ternatea ) was added to improve sensory characteristics. Direct observations of color, aroma, and taste were conducted by the student team, while data related to phytochemical content, antioxidant activity, and antimicrobial properties were compiled from previously published studies. Based on literature sources, rambutan seed tea has been reported to exhibit antioxidant inhibition of approximately 62% and antibacterial activity against Escherichia coli and Staphylococcus aureus. The combination with Butterfly Pea Flower showed higher reported antioxidant activity (up to 75%) and produced a visually appealing purple-blue infusion. Observational results indicated acceptable sensory characteristics among participants. This project highlights the potential of waste valorization as an educational approach to promote environmental awareness and student innovation. The findings suggest that rambutan seed waste can be introduced as a functional herbal tea concept based on existing literature, while simultaneously supporting sustainable waste management and environmental education initiatives.